MARKETING DE SERVIÇOS, UMA SAÍDA ESTRATÉGICA PARA O TRANSPORTE COLETIVO POR ÔNIBUS NO RIO DE JANEIRO - Silva, Maria Edinalva Oliveira da (2004)
This project's aim is to present the Strategic Planning and the concept of marketing of services in the public bus transportation.The research was been in the southern side of Rio de Janeiro. The study raised the present conditions from the public transportation based on different models of analysis of service and the emphasis in the process of quality. The loss of clients in the transport segment was also analysed, as part of the population has low income and consequently they cannot pay the fares and use the buses properly. Some difficulties were mentioned and also problems to finish the studies, besides there are some recommendations to the use of marketing strategies created by the company in order to take some competitive advantages and increase the profits in the service